Biology in Some Fishes in Habiting Water Bodies of India: Assessment of Heavy Metal Concentrations in Fish Species from Water Bodies in India (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The centralizations of substantial metals copper, zinc, lead and iron were estimated in the liver, ngills and muscles of two new water fish species caught from six inspecting destinations in four unique seasons along the course of waterway Jhelum, Kashmir, India. The degrees of hefty metals changed fundamentally among fish species, seasons, locales and organs. True to form, muscle tissue was found to aggregate most reduced groupings of every weighty metal. In the vast majority of the contemplated fish tests, liver was found as the primary objective organ for substantial metal collection. Entomb and intra explicit variety of hefty metals was deciphered for the commitment of potential factors that were found to influence weighty metals take-up, size and weight, geological dissemination and species-explicit variables. For the most part recorded weighty metal focuses were discovered well beneath the admissible furthest reaches of FAOWHO, 1982. The convergence of hefty metals in fish muscle tissue was discovered huge however ok for human utilization.